Financial Policies Supporting Acceleration of Sustainable Economic and Fiscal Growth in Indonesia - Fikry Ramadhan Suhendar; Nurlailiyah Aidatus Sholihah (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2020)
This paper explores the fiscal policy of a country, as well as the policies that influence the economic growth of a country, since the course of government decision-making would be decided by fiscal policy and government expenditure. A research that uses a qualitative descriptive approach and thus a large literature is required to provide information to the government in order to ensure that the government can avoid delaying market prices. Community security can be accomplished when rates can be set by the government. In addition to fiscal policy that can preserve equilibrium, fiscal policy can have an effect on country's economic development and can establish social justice for all societies, followed by fiscal policy in a country through taxes and other responsibilities in Islam such as Zakat. Waqf, as philanthropy, may also help the government's efforts to raise government revenue and is sponsored by top management in the public financial sector, with the expectation that macro and micro businesses may develop in a country.